DETERMINATION UNDER VOLTAGE REDUCTION MINIMUM SPANNING TREE ON ELECTRICITY DISTRIBUTION NETWORK PRIMER - Hadiyanto Hadiyanto; Hardianto Hardianto (Jurnal Ilmiah Teknologi Infomasi Terapan, 2015)
Determination of the minimum spanning tree is widely  used  to  solve  optimization  problems  are problems  that  demand  solutions  minmum  search.  In the  electricity  distribution  network,  the  minimum spanning  tree  (MST)  is  used  to  find  the  minimum cable  length  for  the  system  to  the  power  grid becomes  more  optimal.  The  use  of  a  minimum weight  minimum  cable  length  can  be  used  as  a variable  for  calculating  the  voltage  drop  (voltage drop)  of  an  electricity  distribution  network.   The method  used  in  this  research  is  the  process  of  field observations and data processing. Field observations aims to take some of the coordinates of each pole on the  electricity  distribution  network.  While  the  data processing is done to create a geographic information system that is based on primary data in the form of a power  pole  coordinates  data  and  secondary  data along  with  the  data  in  the  form  of  electricity distribution  networks.  Furthermore,  the  results obtained  by  the  minimum  weight  of  the  MST combined  with  existing  data  on  the  electricity distribution networks like cable  cross-sectional area, the  type  of  cable  used,  and  the  current  through  the tissue  with  voltage  measurement  results  from  the ends  of  the  network  to  obtain  to obtain voltage drop resulting from  each  feeder. Results  (voltage  drop)  can  be  used  as  a  basis  for evaluating the electrical distribution network that has been existing, particularly in the City Bontang.